Ranking Important Factors for Using Postoperative Chemotherapy in Nonmuscle Invasive Bladder Cancer: Conjoint Analysis Results From the Michigan Urological Surgery Improvement Collaborative (MUSIC). Issue 2 (23rd February 2022) - Cary, Clint; Tong, Yan; Linsell, Susan; Ghani, Khurshid; Miller, David C.; Weiner, Michael; Koch, Michael O.; Perkins, Susan M.; Zimet, Gregory
Abstract : Purpose: National and international guidelines recommend the use of 1 dose of intravesical chemotherapy immediately following surgery for nonmuscle invasive bladder cancer, which is performed infrequently on a population level. We sought to understand the importance of potential environmental and clinical dimensions involved in the decision to offer this therapy. Materials and Methods: Urologists from the Michigan Urological Surgery Improvement Collaborative (MUSIC) rated 8 distinct clinical vignettes involving patients with nonmuscle invasive bladder cancer. A ratings-based conjoint analysis method was used to evaluate the clinical vignette responses. Each vignette included 4 clinical dimensions and 2 environmental dimensions, with each dimension consisting of 2 possible attributes. The relative importance of each attribute was derived from the regression model and ranked in order. Results: A total of 58 urologists answered the clinical vignettes which represents >75% of MUSIC sites. The median age of urologists was 53, most were male, and median years in practice was 20 years post residency. An environmental attribute, having a recovery room protocol for instilling and disposing of the chemotherapy, ranked as the most influential attribute for giving postoperative chemotherapy (utility=8.6). The clinical attribute yielding the strongest preference for giving chemotherapy was tumor grade (utility=4.9). These preferences varied by different subgroups of urologists, particularly regarding the type of practice a urologist was in. Conclusions: This study demonstrates that urologists have clear preferences for when they offer postoperative immediate chemotherapy. Factors beyond just clinical variables play a role in this decision making process such as the structure of the recovery room.